Watching the Watchdogs: A Conceptual Model for Media Accountability in a Non-Western Country. (21st April 2023) - Zaid, Bouziane; Shin, Don Donghee; El Kadoussi, Abdelmalek; Ibahrine, Mohammed
ABSTRACT: Professional and academic debates on the role of media accountability instruments (MAIs) have so far largely focused on Western democracies and on solving the issues of transparency and trust through press and media councils, ombudspersons, media criticism fora, and digital forms of media accountability. They have notably ignored the disruptive force of media technologies in the context of the rise of algorithm-driven platforms. This paper draws on Von Krogh [Von Krogh, T. 2012. Understanding Media Accountability Media Accountability in Relation To Media Criticism and Media Governance in Sweden 1940–2010 . PhD Diss. Mid Sweden University] amended version of McQuail (2005) and Bardoel and d'Haenens' models (2004. "Media Responsibility and Accountability: New Conceptualizations and Practices." Communications 29: 5–25. doi:10.1515/comm.2004.007) to propose an enhanced model that takes into account the state/media relations in non-democratic societies and the disruptive force of media technologies and algorithm-driven platforms. In-depth semi-structured interviews with 12 prominent media practitioners were conducted. The findings suggest the limits of normative conceptualizations of media accountability when adopted and applied to non-democratic countries. We propose a model that explains the role of media technologies and algorithms-driven platforms as game changers in the debate on media accountability in non-Western countries.